From the “old” Cepalism to the criticism of Globalization Change and continuity in the debate over development strategiesin Latin America (2008)
The idea of development was branded more by practical elements than by conceptual intentions, and has been therefore “development policy”. This article starts from that position and offers a brief on the debate, from the cepaline thought of the 50’s over